Mercantilism as Strategic Trade Policy: The Anglo-Dutch Rivalry for the East India Trade - Irwin, Douglas A. (Journal of Political Economy, 1991)
This paper interprets seventeenth-century mercantilism in light of recent theories of strategic trade policy. Long-distance international commerce during the mercantilist period was undertaken chiefly by state-chartered monopoly trading companies and was therefore conducted under conditions of imperfect competition. The economic structure of the Anglo-Dutch rivalry for the East India trade provides an excellent illustration of an environment in which the profit-sharting motive for strategic trade policies exists. Dutch supremacy in the early East India trade was facilitated by a managerial incentive scheme in the monopoly charter that enabled it to achieve a Stackelberg leadership position against the English. Using data from the East India trade around 1620 in a Cournot duopoly model, I find that the managerial incentives yielded greater Dutch profits than would have been obtained from a standard profit-maximizing objective and that the scope for other strategic trade policies was clearly present.